Analisis Geospasial Penentuan Lokasi TPA Sampah di Kabupaten Kerinci - Susanti, Yuli; Triyatno, Triyatno (Al-DYAS, 2024)
The purpose of this research are : 1) To analyze suitable locations for the construction of landfill sites in Kerinci Regency based on SNI Number 03-3241-1994 using a Geographic Information System (GIS), 2) To analyze the suitability of the recommendations for selected landfills based on SNI Number 03 -3241-1994 with Kerinci Regency Regional Spatial Planning (RTRW) Map. This type of research uses quantitative descriptive methods. The results of the research are: 1) the recommended locations for landfill construction are in 3 sub-districts, including Keliling Danau Sub-district with an area of 883 ha, Batang Merangin Sub-district with an area of 1,283 ha, and Siulak Mukai Sub-district with an area of 209 ha. 2) The three selected landfill recommendations are not located in areas planned as residential areas. The three locations that meet the criteria as landfill locations have been planned as plantation areas and permanent production forest areas.